2008
DOI: 10.1007/s11046-008-9167-3
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Herbs Drugs: Inhibitory Effect on Growth of the Endogenous Mycoflora and Aflatoxin Production

Abstract: Twenty commercial mixed herbal drugs were examined for mycological profile. Aspergillus species were the predominant fungi found in the drugs. Other fungi harboured in the drugs with less frequency were Paecilomyces species, Eurotium species, Monascus species, Acremonium species, Penicillium species, Cladosporium species, Scopulariopsis species, Phialophora species and Fonseceae species. Fungal count was between 1.0 log(10) CFU and 2.4 log(10) CFU per gram of sample. When the drugs were incubated in 85% humidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For many centuries, medicinal herbs have been used to treat diseases ranging from autoimmune diseases to cancer (Cundell et al, 2003;Kusunoki et al, 2004;Cassileth et al, 2008;Razaki et al, 2009). Animal experiments and modern clinical trials have shown that many of these herbs have immunomodulatory properties (Yale and Liu, 2004;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For many centuries, medicinal herbs have been used to treat diseases ranging from autoimmune diseases to cancer (Cundell et al, 2003;Kusunoki et al, 2004;Cassileth et al, 2008;Razaki et al, 2009). Animal experiments and modern clinical trials have shown that many of these herbs have immunomodulatory properties (Yale and Liu, 2004;Wang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…10 grams of powdered leaves were made soluble with 100 ml distilled water at 200 rpm for 5 h at room temperature. 23 The remaining insoluble material was filtered by Whattman No.1 filter paper and centrifuged at 10,000 rpm for 10 min. The supernatant was collected and again passed through 0.45 µm filter (Millipore) and stored at -20°C for further use.…”
Section: Collection and Preparation Of Aqueous Plant Extractsmentioning
confidence: 99%
“…The citrinin was extracted three times with chloroform (1:1 v/v), pooled and concentrated in vacuo at 40°C using a rotary evaporator. The crude extract was diluted in minimum amount of chloroform (2 ml) and citrinin was estimated by thin layer chromatography (TLC) according to Razak et al [19] with minor modifications. Briefly, different volumes (1 to 5 µl) of sample extracts were applied to precoated TLC plates (TLC Silica gel 60 F254, Merck, Germany) along with standard (containing citrinin at 0.5 µg/ml).…”
Section: Mossini and Kemmelmeiermentioning
confidence: 99%
“…Then the leaves were dried in hot air oven at 60C for 4 days and ground to made powder to pass through 20 mesh sieve. Ten grams of ground powder were shaken in 100 ml distilled water at 200 rpm for 5 h at room temperature [19]. The insoluble material was filtered by Whatman No.1 filter paper and centrifuged at 10,000 rpm for 10 min.…”
Section: Aqueous Extracts Of Five Medicinal Plantsmentioning
confidence: 99%